Teaching microeconomics with Islamic perspectives an introduction - Barom, Mohd Nizam; Imon, Riasat Amin; Haneef, Mohamed Aslam (Centre for Islamic Economics, Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia and International Institute of Islamic Thought, 2024)
As a continuation from the first volume in the ‘Islamic Economics Education in Southeast Asia’ series which emphasised on the issue of Islamic economics curriculum, this present volume attempts to provide an insight into the experience, challenges, lessons learned, as well as initiatives to carry forward the Islamic economics education agenda in the teaching of microeconomics. It covers some important considerations for the integration process in the teaching of microeconomics, as well as a number of case studies of the experiences of teaching microeconomics with Islamic perspectives in selected Southeast Asian universities.